Analisis Curah Hujan Menggunakan Machine Learning Metode Regresi Linier Berganda Berbasis Python dan Jupyter Notebook - jesi pebralia (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2022)
Indonesia is a country located on the equator. As a result, Indonesia has a dry season and a rainy season. Rainfall prediction is very useful in various fields. The prediction method that is currently developing rapidly is the prediction method using artificial intelligence (AI) techniques. Machine learning is a subset of AI. The application of multiple linear regression algorithms in machine learning can be used to predict a dependent variable with various types of independent variables that affect it. In this study, rainfall prediction has been carried out involving three independent variables, namely wind speed, maximum air temperature, and minimum air temperature with dataset obtained from the kaggle.com site. The dataset used is 6,574 data, where the data is grouped into training data as much as 80% and test data as much as 20%. Multiple linear regression algorithm is written in Python programming language and implemented using jupyter notebook. In this study, a multiple linear regression model was produced with the equation ,, MSE value was 14.02, RMSE was 3.74, and MAE was 2.27.